On the Foundation Period of the Maronite Tradition - Azize, Joseph (Religions, 2024)
The Maronite Church states that it is an Antiochene and Syriac Church. This article traces, in chronological and discursive fashion, the emergence of the Maronite tradition. It explores the life and significance of St Maroun (d. ca AD 418–23), giving consideration to thinkers who helped to understand his outlook and methods and assessing what we know of the St Maroun monastery (Dayr Mar Maroun) and its vicissitudes down to the sixth century. The piece then treats Maronites in the context of the seventh-century monothelite controversy, following their foundational developments up to the time of their first patriarch Yohanna Maroun (flor. 680s). The paper considers not only the ascetic and monastic currents in the early Maronite community but also touches on the influence of Syriac typology and its gradual displacement by analytic and dogmatic theology.